Development, structure and in vitro digestibility of type 3 resistant starch from acid-thinned and debranched pea and normal maize starches. (15th July 2020) - Li, Liying; Yuan, Tommy Z.; Ai, Yongfeng
Highlights: RS3 was developed from acid-thinned and debranched starch at 25% dry solids content. The yield of pea RS3 (68.1%) was higher than that of normal maize RS3 (59.6%). Pea and normal maize RS3 exhibited the B-type X-ray diffraction pattern. Pea RS3 was less digestible by amylolytic enzymes compared with normal maize RS3. Pea RS3 showed greater thermal stability than normal maize RS3. Abstract: Type 3 resistant starch (RS3) was developed from native pea starch through acid thinning, debranching and recrystallization, and the resultant pea RS3 was then characterized and compared with that generated from native normal maize starch. Starting from the respective native starches, the modification method yielded 68.1% of RS3 from pea and 59.6% from normal maize. The particles of pea and normal maize RS3 showed a coarse surface and irregular shapes and sizes. Both pea and normal maize RS3 displayed the B-type X-ray diffraction pattern, with 41.0% and 37.7% relative crystallinity, respectively. In vitro starch digestibility assay revealed that pea RS3 – in both uncooked and cooked states – was less digestible by amylolytic enzymes than normal maize RS3 because the former possessed double-helical crystallites of a more compact structure. The information presented in the study is valuable for the development of RS ingredient from pea starch for food applications.